Dancing Bodies of Devotion: Fluid Gestures in Bharata Natyam - Zubko, Katherine C. (Lexington Books, 2014)
Dancing Bodies of Devotion: Fluid Gestures in Bharata Natyam examines how Bharata Natyam, a traditionally Hindu storytelling dance form, moves across religious boundaries through both incorporating choreography on Buddhist, Christian, Muslim, and Jain themes and the pluralistic identities of participants. Dancers traverse religious boundaries by reformulating an aesthetic foundation based on performative rather than solely textual understandings of rasa, conventionally defined as a formula for how to physically craft emotion on stage. Through the ethnographic case studies of this volume, dancers of Bharata Natyam innovatively demonstrate how the rasa of devotion (bhakti rasa), surprisingly absent from classic dance-related texts, serves as the pivotal framework for expanding on their own interreligious thematic and interpretive possibilities. In contemporary Bharata Natyam, bhakti rasa is not just about enhancing religious experience; instead, these dancers choreographically adapt various religious identities and ideas in order to emphasize pluralistic cultural and ethical dimensions in their work. Through the dancing body, multiple religious and secular interpretations fluidly co-exist.